2019
DOI: 10.1002/jmri.26669
|View full text |Cite
|
Sign up to set email alerts
|

Absence of dentate nucleus resting‐state functional connectivity changes in nonneurological patients with gadolinium‐related hyperintensity on T1‐weighted images

Abstract: Background The dentate nuclei of the cerebellum are the areas where gadolinium predominantly accumulates. It is not yet known whether gadolinium deposition affects brain functions. Purpose/Hypothesis To assess whether gadolinium‐dependent high signal intensity of the cerebellum on T1‐weighted images of nonneurological adult patients with Crohn's disease is associated with modifications of resting‐state functional connectivity (RSFC) of the cerebellum and dentate nucleus. Study Type Observational, cross‐section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 50 publications
2
23
0
1
Order By: Relevance
“…Concerns over NSF and, more recently, Gd retention have led to a widespread migration from linear GBCAs to macrocyclic GBCAs for routine clinical use. Although studies to date suggest that GBCA exposure has no long‐term detrimental effects on human health either in terms of direct impact on tissue integrity, or global clinical disability, the possibility of long‐term effects is nevertheless a major area of current concern . Although assessment of potential long‐term safety issues was beyond the scope of this observational study, it is worth noting that all studies thus far performed in animals to evaluate Gd retention in brain and body tissues following GBCA exposure have shown that gadoteridol is retained to a lesser extent and cleared more rapidly than other GBCAs, including other macrocyclic GBCAs .…”
Section: Discussionmentioning
confidence: 99%
“…Concerns over NSF and, more recently, Gd retention have led to a widespread migration from linear GBCAs to macrocyclic GBCAs for routine clinical use. Although studies to date suggest that GBCA exposure has no long‐term detrimental effects on human health either in terms of direct impact on tissue integrity, or global clinical disability, the possibility of long‐term effects is nevertheless a major area of current concern . Although assessment of potential long‐term safety issues was beyond the scope of this observational study, it is worth noting that all studies thus far performed in animals to evaluate Gd retention in brain and body tissues following GBCA exposure have shown that gadoteridol is retained to a lesser extent and cleared more rapidly than other GBCAs, including other macrocyclic GBCAs .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the absence of changes in ADC values between patients exposed to brain irradiation and the control group, we observed a relationship between higher ADC values and shorter time after WBRT. From a biological standpoint, this finding might reflect early and subtle posttreatment vasogenic edema with weakening of the blood–brain barrier, possibly explaining the previously reported effects of radiation therapy on T 1 DN‐to‐pons ratios in patients exposed to GBCAs 13,14,21 . Indeed, a recent study based on a murine model with analysis of DWI and MRI dynamic contrast‐enhanced imaging, before and 24 hours after three daily fractions of 4 Gy whole‐brain radiotherapy, showed increased ADC values together with higher permeability (parameter K trans ) in the treated metastatic tumors 30 .…”
Section: Discussionmentioning
confidence: 77%
“…This has been challenged by observations that unenhanced T 1 signal intensity increases with normal myelination as children mature, and by underlying pathological processes, which may complicate the interpretation of increasing unenhanced T 1 signal intensity as indicative of Gd deposition in patients who undergo multiple MRI examinations over time . No adverse clinical or pathological consequences of Gd deposition in the brain have thus far been confirmed . However, precautionary recommendations have been made in the use of linear GBCA by professional organizations and the Food and Drug Administration .…”
Section: Discussionmentioning
confidence: 99%
“…This has led to a new concern that linear GBCA, which undergoes dechelation, results in Gd deposition in many tissues, including the brain and bone. The significance of this concern has been challenged by the broad radiology community and lack of current clinical evidence of deleterious effects . However, linear GBCA have been largely withdrawn in Europe in favor of macrocyclic agents, which do not undergo dechelation .…”
Section: Introductionmentioning
confidence: 99%